Antifungal Activity of Topical Microemulsion Containing Ziziphus spina-christi L. for the Treatment of Fungal Vaginitis: Antifungal Activity of Microemulsion Containing Ziziphus spinachristi L - Salimi, Anayatallah; Shirani, Maryam (Iranian Journal of Pharmaceutical Sciences, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida albicans and other Candida species is a high-risk event in patients admitted to hospital. Ziziphus genus is a rich source of medicinal compounds, effective for the treatment or prevention of some diseases. This study aimed to evaluate the antifungal effect of topical microemulsion containing Ziziphus spina-Christi L (ZSC) extracts against Candida spp. Z. Spina-Christi was collected and extracted in a Soxhlet apparatus using the ethanol and methanol solvents. Microemulsions were formulated by the composition of surfactant (Tween 80) along with cosurfactant (propylene glycol), oil, and water and were characterized regarding their stability. The The in vitro antifungal study was performed by measuring and comparing the diameter of zones of inhibition (in mm) against C. albicans (ATCC 3153), C. parapsilosis (ATCC 2195) and C. krusei (ATCC 573) using agar well diffusion test, for the various formulations (without extract and containing ZSC extract). The optimal microemulsion was analyzed for the average diameter of droplets, pH, viscosity and zeta potential. The microemulsion containing Ziziphus spina-Christi ethanolic extract had a significant inhibitory effect on the different species of Candida, but the most inhibitory effect was found against C. albicans. The result showed that the ethanolic extract in microemulsion was Light green and, average globule size was 2.93 mm, no separation after centrifugation at 3000 rpm for 30 min, pH at 3.8, and viscosity was 8.523cps. The results of this study indicate that the ethanolic extract has interesting antifungal properties and can used for the treatment of fungal infections. More research is required to check this plant performance to treat the patients with Candidiasis.